Life cycle assessment of domestic hot water systems: a comparative analysis. Issue 2 (2nd April 2016) - Piroozfar, Poorang; Pomponi, Francesco; Farr, Eric R.P.
Abstract : On average, hot water is responsible for 18% of residential energy consumption and corresponding greenhouse gas (GHG) emissions. Several domestic hot water systems (DHWSs) are commonly used but their life cycle impacts are yet to be established comprehensively. This is due to those impacts varying significantly within the context and the system boundaries of the assessment. This article reports findings from a comparative cradle-to-grave life cycle assessment (LCA) of five DHWSs in the UK context. Primary data acquired from a case study contributed to achieving accurate life cycle inventories that were then modelled in SimaPro through the ecoinvent database. Global Warming Potential (GWP) is the impact assessment method used. Amongst the five types, solar heater with electric backup appears to be the least damaging alternative. The study also reinforces the importance of adopting a cradle-to-grave approach if LCA results are to accurately reflect environmental impacts holistically and lead to better, more informed decisions.